Preparation and characterization of natural rubber/clay, poly (ethylene-co-vinyl acetate)/clay nanocomposites - Sharif, Jamaliah (2005)
This thesis describes the preparation, characterization and physicochemical properties of natural rubber/clay, poly(ethylene-co-vinylacetate)/clay and natural rubber/poly(ethylene-co-vinyl acetate)/clay nanocomposites. In order to improve the clay and polymer compatibility, the clay was first converted into the organoclay. The organoclays were prepared from sodium montmorillonite (Na-MMT) through cation exchange reaction using cetyltrimethyl ammonium bromide, octadecyl ammonium chloride or dodecyl ammonium chloride. The x -ray diffraction (XRD) results reveal that the interlayer distance of the Na-MMT increases with the formation of the organoclays. The presence of the alkyl ammonium ions in the organoclays was also studied by the Fourier transforms infrared spectroscopy (FTIR). The amount of alkyl ammonium ions intercalated into the clay galleries increases with the increase of alkyl ammonium chain length as shown by elemental analysis and thermogravimetric analysis (TGA) results.The nanocomposites were prepared by melt blending the natural rubber (NR), poly (ethylene-eo-vinyl acetate) (EVA) or blend of both NR and EVA with the organoc1ays. The compounds were then crosslinked with an electron beam (EB) irradiation. The XRD patterns showed that all of the nanocomposites produced from this work are of intercalated-type. These were further confirmed by transmission electron microscopy (TEM) observation. Scanning electron microscopy (SEM) study on the cryo-fractured surface reveals that the pure Na-MMT dispersed in the polymer matrix in large agglomerated form while the modified Na-MMT separated into small aggregates and dispersed homogeneously in the polymer matrix. The optimum irradiation dose for crosslinking of NR, EVA and NR/EVA nanocomposites was determined. The formation of radiation induced crosslinking in NR, EVA and NR/EVA blend was not inhibited with the presence of dodecyl ammonium montmorillonite (DDA-MMT) but it was affected by the presence of dimetyl dehydrogenated tallow montmorillonite (C20A). The tensile modulus of all the nanocomposites increases with the increase of the clay content of up to 10 phr. The tensile strength and elongation at break of the NR/clay nanocomposites increases with the increase of organoc1ays up to 3 phr and decreases with further increase of the organoc1ay content. However, the tensile strength of EVA/clay and NR/EVA/clay nanocomposites remains constant with the increase of the organoclay content of up to 5 phr but decreases with the increase of organoclay content of up to 10 phr. The elongation at break of both EVA/clay and NR/EVA/clay decreases slightly with the increase of organoc1ay content. Electron beam irradiation of the nanocomposites increases the tensile modulus and tensile strength further but decreased the elongation at break.